2018
DOI: 10.7717/peerj.5109
|View full text |Cite
|
Sign up to set email alerts
|

Patients with chronic periodontitis present increased risk for primary Sjögren syndrome: a nationwide population-based cohort study

Abstract: Many reports have mentioned the association between chronic periodontitis (CP) and primary Sjögren syndrome (pSS). However, no cohort study has been performed for the risk of pSS in patients with CP. In this study, we evaluated the risk of pSS from CP exposure in a nationwide population-based cohort study in Taiwan. We studied the claims data of Taiwanese population from 2001 to 2012. We identified 76,765 patients with CP from the National Health Insurance Database in Taiwan. We also selected 76,765 controls t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…All in all, the results we get may lean toward “correlation.” In addition, we tried to search the studies on the incidence of Sjogren’s syndrome in patients with periodontal disease. Unfortunately, due to the retrieval of only two articles ( 47 , 48 ), meta-analysis could not be conducted, and further relationship could not be obtained. However, both papers concluded that patients with periodontal disease were more likely to have Sjogren’s syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…All in all, the results we get may lean toward “correlation.” In addition, we tried to search the studies on the incidence of Sjogren’s syndrome in patients with periodontal disease. Unfortunately, due to the retrieval of only two articles ( 47 , 48 ), meta-analysis could not be conducted, and further relationship could not be obtained. However, both papers concluded that patients with periodontal disease were more likely to have Sjogren’s syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Nikitakis et al (2017) suggested that a dysregulated immune response against the oral microbiome in Sjögren’s patients could be responsible for initiating an autoimmune response in Sjögren’s or involved in its amplification. A Taiwanese case-control study of chronic periodontitis patients, identified from the National Health Insurance Database frequency matched by age, sex, and index year to a cohort from the general population, showed the incidence of Sjögren’s (8.5 y later) was significantly higher in the chronic periodontitis cohort (hazard ratio, 1.79; Lin et al 2018). Szymula et al (2014) in a laboratory study found that the von Willebrand factor type A (vWFA) domain protein produced by Capnocytophaga ochracea was the most potent activator of SSA (Ro).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed the interaction between EB nuclear antigen 2 (EBNA2) and genetic loci associated with RA, EBNA-1 and Ro-60 antigen in SS [34,35]. Besides, a strict relationship between chronic periodontitis and RA and a verified association between chronic periodontitis exposure and SS risk have also been demonstrated [36,37].…”
Section: Environmentmentioning
confidence: 99%